Duration of feed application of mixed powders of Phyllanthus niruri and Allium sativum for the prevention of Aeromonas hydrophila infection in catfish Clarias sp. - Wahjuningrum, Dinamella; Widiani, Iis; Nuryati, Sri (Indonesian Society of Scientific Aquaculture (ISSA), 2012)
Motile Aeromonad Septicaemia (MAS) caused by Aeromonas hydrophila induced serious epidemics of disease in catfish Clarias sp. The purposed of this research was to determine optimum durations of feed application of mixed powders Phyllanthus niruri and Allium sativum to prevent MAS. Experimental design that used was Complete Random Design which consist of three treatments and three replications. This research tested on three different of durations of feed application of P. niruri and A. sativum, namely A (powder of P. niruri and A. sativum feed application during 21 days and infected with A. hydrophila 0,1 mL IP), B (powder of P. niruri and A. sativum feed application during 14 days and injected IP with A. hydrophila 0,1 mL), C (powder of P. niruri and A. sativum feed application during seven days and injected IP with A. hydrophila 0,1 mL), and control, namely K- (without P. niruri and A. sativum feed application and injected IP with PBS 0,1 mL) and K+ (without P. niruri and A. sativum powder application and injected IP with A. hydrophila 0,1 mL). The treatments was given for 21 days before challenging test, at 22th day test in vivo carried out by injecting A. hydrophila (108 CFU/mL) into the fish by intramuscular and observed for 10 days. The highest value of survival rate that consist in treatment K- was 100±0.00%, treatment A was 93.3±11.55%, and treatment B was 73.33±30.55%. While treatment K+ and C have the same survival rate that is, 26.67±11.55%. The application P. niruri and A. sativum powder during 21 days was optimum for preventing MAS in catfish.Keywords: Phyllanthus niruri, Allium sativum, Aeromonas hydrophila, Clarias sp.